Politics, credit allocation and bank capital requirements - Thakor, Anjan V. (Journal of Financial Intermediation, 2021)
I develop a normative theory of political influence on bank lending and capital structure. Legislators want banks to make politically-favored loans that reduce bank profits but generate social or political benefits. The regulator uses asset-choice regulation and capital requirements to induce the lending desired by legislators. There are four main results. First, if regulators dislike bank fragility, then credit-allocation regulation should be accompanied by higher capital requirements. Second, banks will resist higher capital requirements, which will be lower when banks have more bargaining power. Third, when politics matters more in bank regulation, the banking sector is larger and more competitive, with higher capital requirements. Fourth, the optimal reporting mechanism, in which banks report their privately-known profitability and the regulator endogenously determines capital requirements and stringency of credit-allocation regulation in response, shows that political influence is stronger when banks are more profitable.